Long-term quality of life after peroral endoscopic myotomy remains compromised in patients with achalasia type III - Hernández Mondragón, Oscar V.; González Martinez, Marina A.; Blancas Valencia, Juan M.; Hernandez Reyes, Maria L.; Solórzano Pineda, Omar M.; Blanco Velasco, Gerardo (Endoscopy, 2017)
Background and study aims Peroral endoscopic myotomy (POEM) is an excellent endoscopic treatment for achalasia. Clinical and manometric parameters are used for evaluation and follow-up. However, clinical success does not guarantee high quality of life (QoL) scores, generating doubts about their direct relationship. We aimed to evaluate QoL scores before and after POEM at medium and long term, to evaluate differences between achalasia subtypes and find which factors related to low QoL scores. Patients and methods Achalasia-confirmed patients undergoing POEM between February 2012 and November 2016. and completing at least 1 year of follow-up, were included. Assessment before and at 1, 6, 12, 24, 36 and 48 months after POEM employed manometry, barium series, Eckardt score, and the AE-18 health-related QoL scale. Demographic, clinical, and procedure characteristics were documented, with comparisons between subgroups. Multiple logistic regression analysis was done. Results 65 of 88 patients were included (38 women, 27 men; median age 47 years, interquartile range [IQR] 20 – 81), and 50 (76.9 %) completed 4 years of follow-up. Eckardt score improved (median, preprocedure 10 vs. post-procedure 2; P = 0.002) and this persisted. There was initial improvement in median integrated relaxation pressure (IRP) (29.4 mmHg [16 – 55] vs. 10.3 mmHg [3 – 18]; P = 0.000) and median QoL scores (40 vs. 68 at 1 month; P = 0.002); however IRP increased and QoL scores decreased. Men with confirmed type III achalasia had low QoL scores.Conclusions All patients had significant clinical improvement after POEM, with medium- to long-term persistence. Though quality of life and IRP initially improved, they deteriorated in the long term. Male sex and type III achalasia seem to be associated with low QoL scores.